2004
DOI: 10.1016/s0006-3495(04)74358-1
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Structural Role of Carotenoids in the Photosystem I: A Quantum Chemical Analysis

Abstract: The structural stabilization role of carotenoids in the formation of photosynthetic pigment-protein complexes is investigated theoretically. The pi-pi stacking and CH-pi interactions between beta-carotenes and their surrounding chlorophylls (and/or aromatic residues) in Photosystem I (PS1) from the cyanobacterium Synechococcus elongatus were studied by means of the supermolecular approach at the level of the second-order Møller-Plesset perturbation method. PS1 features a core integral antenna system consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 68 publications
2
28
0
2
Order By: Relevance
“…We may also expect that the interaction between BChl and carotenoid molecules is weaker in C. aurantiacus than in C. tepidum because the carotenoids present in C. aurantiacus (mainly ␤-carotene and ␥-carotene) do not contain end groups but ␤-rings, with two out-of-plane methyl substituents. In this case, a CH-interaction seems to be responsible for the attractive interaction between the carotenoid end ring and the conjugated system of the BChl molecule (36). CH-interaction is weaker than the -interaction, and therefore, ␤-carotene is more easily removed by hexane than chlorobactene.…”
Section: Discussionmentioning
confidence: 99%
“…We may also expect that the interaction between BChl and carotenoid molecules is weaker in C. aurantiacus than in C. tepidum because the carotenoids present in C. aurantiacus (mainly ␤-carotene and ␥-carotene) do not contain end groups but ␤-rings, with two out-of-plane methyl substituents. In this case, a CH-interaction seems to be responsible for the attractive interaction between the carotenoid end ring and the conjugated system of the BChl molecule (36). CH-interaction is weaker than the -interaction, and therefore, ␤-carotene is more easily removed by hexane than chlorobactene.…”
Section: Discussionmentioning
confidence: 99%
“…Crystalline ␤-carotene has C i symmetry with a conjugated backbone that lies almost entirely on the xy plane except for end groups that are twisted out of plane. 93,94 ͑In the biological setting, carotenoid pigments usually adopt a twisted configuration in the conjugated backbone 95,96 ͒. There are 11 conjugated double bonds in the backbone.…”
Section: Discussionmentioning
confidence: 99%
“…These carotenes were bound at the surfaces of PsaA, PsaB, and several small subunits (Jordan et al 2001) and are suggested to play a structural role as a ''hydrophobic glue'' in stabilizing the multi-subunit PSI core complex by interactions with their surrounding chlorophylls and aromatic residues (Fromme et al 2003;Wang et al 2004). Two important implications for the replacement of b-carotene by a-carotene and e-carotene can be considered.…”
Section: Organization Of Lhca Antennas In Psi-lhci Of B Corticulansmentioning
confidence: 99%